The Effect Of Teaching – Cognitive Program On The Development Of Some Handball Skill In Second Year Students Of Secondary School - Hussein, Eman; Ali, Riaad (Journal of Physical Education, 2016)
The problem of the research lies in answering the following question; will a cognitive – teaching program develop the students’ level in learning some handball skills. The aim of the research is preparing a teaching – cognitive program for teaching some basic skills in handball in secondary school students as well as identifying the effect of this program on developing some basic skills in handball. The researchers hypothesized statistical differences between pre and posttests of controlling and experimental groups as well as differences in posttests of both groups. The researchers used the experimental method. The subjects were (30) male secondary school students from Al Sherqia School and divided them into two equal groups; controlling and experimental. Pretests as well as the training program were applied on the subject followed by the posttests. The data was collected and treated using roper statistical methods. The results showed the positive effect of the training program on developing skills and achievement. The researchers recommended conducting similar researchers on different age groups as well as using this program in secondary schools. Finally they recommended using cognitive teaching as an extra means for developing skills and achievements in students